Challenges in establishing animal models for studying osteoimmunology of hypoparathyroidism - Butylina, Maria; Föger-Samwald, Ursula; Gelles, Katharina; Pietschmann, Peter; Sipos, Wolfgang (Frontiers in Veterinary Science, 2023)
Hypoparathyroidism is a relatively rare human and veterinary disease characterized by deficient or absent production of parathyroid hormone (PTH). PTH is known as a classical regulator of calcium and phosphorus homeostasis. Nevertheless, the hormone also appears to modulate immune functions. For example, increased CD4:CD8 T-cell ratios and elevated interleukin (IL)-6 and IL-17A levels were observed in patients with hyperparathyroidism, whereas gene expression of tumor necrosis factor-α (TNF-α) and granulocyte macrophage-colony stimulating factor (GM-CSF) was decreased in patients with chronic postsurgical hypoparathyroidism. Various immune cell populations are affected differently. So, there is a need for validated animal models for the further characterization of this disease for identifying targeted immune-modulatory therapies. In addition to genetically modified mouse models of hypoparathyroidism, there are surgical rodent models. Parathyroidectomy (PTX) can be well performed in rats—for pharmacological and associated osteoimmunological research and bone mechanical studies, a large animal model could be preferable, however. A major drawback for successfully performing total PTX in large animal species (pigs and sheep) is the presence of accessory glands, thus demanding to develop new approaches for real-time detection of all parathyroid tissues.